PROTOONCOGENE - Lusiani Tjandra (Universitas Wijaya Kusuma Surabaya, 2010)
Genes that promote autonomous cell growth in cqncer cells are called oncogenes, and their normal cellular counterparts are called protooncogenes. Protooncogenes are physiologic regulators of cell proliferation and differentiation,oncogenes are characterized by the ability to promote cell growth in the absence of normal mitogenic signals. Their products, called oncoproteins, resemble the normal products of protooncogenes with the exception that oncoproteins are devoid of important regulatory elements.Their production in the transformed cells becomes constitutive, that is, not dependent on growth factors or other external signal. Each of the cancer genes has a specific function, the dysregulation of which contributes to the origin or progression of malignancy. It traditional to describe cancer- causing genes on the basis of their presumed function.Mutations in genes that regulate these cellular traits are seen in every cancer. However, the precise genetic pathways that give rise to these attributes differ between cancers, even within the same orhan. It is widely believed that the occurrence of mutations in cancer-causing genes is conditioned by the robustness of the DNA repair machinery of the cell. When genes that normally sense andrepair DNA demage are impaired or lost, thevresultant genomic instability favors mutations in genes that regulate the other acquired capabilities of cancer cells.